PENGEMBANGAN METODE ANALISIS PERFORMA SALURAN UDARA TEGANGAN EKSTRA TINGGI (SUTET) 500kV TERHADAP SAMBARAN PETIR STUDI KASUS : SALURAN UDARA TEGANGAN EKSTRA TINGGI 500kV CAWANG BARU – BEKASI - Yandri Paulus Marbun (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study evaluates the performance of the 500 kV Cawang Baru–Bekasi Extra High Voltage Transmission Line (SUTET) under lightning-induced impulse voltages. Given Indonesia’s high lightning density, lightning strikes were modeled probabilistically using Monte Carlo simulations based on FALLS data (2018–2024). The model achieved good accuracy (MAPE: 14% for strike probability, 12% for density, and 7% for current probability). Tower vulnerability was classified into three categories based on lightning density (N_g). Key factors causing impulse voltage to exceed BIL—triggering back flashover—include lightning current magnitude, ground resistance, and tower inductance. Findings highlight the need for optimizing grounding systems and lightning protection through probabilistic analysis to enhance transmission reliability.